2003
DOI: 10.1177/08830738030180061301
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Early-Onset Huntington's Disease

Abstract: Huntington's disease is an autosomal dominant progressive neurodegenerative disorder characterized by involuntary movements, cognitive decline, and behavioral disorders leading to functional disability. In contrast to patients with adult onset, in which chorea is the major motor abnormality, children often present with spasticity, rigidity, and significant intellectual decline associated with a more rapidly progressive course. An unusual early-onset Huntington's disease case of an 11-year-old boy with severe h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
10
0
4
Order By: Relevance
“…Although both the early- and adult-onset forms of HD are characterized by dementia, movement disorder, and personality changes, juvenile HD patients do not display chorea as adult-onset patients. Instead, juvenile HD patients are often rigid and stiff and exhibit severe cognitive dysfunction and seizure that is not seen in adult HD patients (Vargas et al, 2003; Squitieri et al, 2006). In the brains of juvenile HD patients, there are more nuclear aggregates and fewer neuropil aggregates than in adult HD brains (DeFiglia et al, 1997; Gutekunst et al, 1998), and also more widespread degeneration, suggesting that polyQ repeat lengths mediate different pathogenic pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both the early- and adult-onset forms of HD are characterized by dementia, movement disorder, and personality changes, juvenile HD patients do not display chorea as adult-onset patients. Instead, juvenile HD patients are often rigid and stiff and exhibit severe cognitive dysfunction and seizure that is not seen in adult HD patients (Vargas et al, 2003; Squitieri et al, 2006). In the brains of juvenile HD patients, there are more nuclear aggregates and fewer neuropil aggregates than in adult HD brains (DeFiglia et al, 1997; Gutekunst et al, 1998), and also more widespread degeneration, suggesting that polyQ repeat lengths mediate different pathogenic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that in Huntington’s disease (HD), polyQ repeats larger than 60 glutamines cause juvenile cases, who display different symptoms and have more widespread degeneration in the brain. For example, juvenile HD patients do not display chorea, but they have severe cognitive dysfunction and seizure that is absent in adult HD patients (Vargas et al, 2003; Squitieri et al, 2006). Juvenile HD patient brains also have more nuclear aggregates, whereas adult HD brains have more neuripil aggregates, also suggesting that polyQ lengths mediate different pathogenic pathways (DeFiglia et al, 1997; Gutekunst et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…However, this literature survey was conducted before the availability of genetic testing to confirm the diagnosis. Review of the literature revealed only 12 cases of genetically confirmed JHD with reported seizures, only 5 of which had accompanying EEG data 5–8. Seizure type, EEG findings, and response to antiepileptic drugs were highly variable across the rare published cases, and the paucity of available data precludes drawing meaningful conclusions.…”
mentioning
confidence: 99%
“…A evolução cursa com piora do quadro cognitivo, psiquiátrico e com surgimento de sintomatologia motora 4,7 . A família também pode relatar como primeiros sintomas motores dificuldade de deambular, quedas frequentes, bem como disartria 6,12,20,21,22 . A instabilidade postural em associação com quedas, sinais piramidais e regressão cognitiva pode levar ao diagnóstico diferencial de síndrome de regressão idiopática 22 .…”
Section: Dicussãounclassified
“…A família também pode relatar como primeiros sintomas motores dificuldade de deambular, quedas frequentes, bem como disartria 6,12,20,21,22 . A instabilidade postural em associação com quedas, sinais piramidais e regressão cognitiva pode levar ao diagnóstico diferencial de síndrome de regressão idiopática 22 . Também podem ocorrer convulsões sem histórico prévio 10,11,17 .…”
Section: Dicussãounclassified